Las enfermedades en corales escleractínidos: ¿Un nuevo problema en el arrecife de Cayo Sombrero, Parque Nacional Morrocoy, Venezuela? - Cróquer, Aldo (2003)
At the beginning of 1996 coral reefs in Morrocoy National Park, Venezuela, suffered an unprecedented mass mortality event. As a consequence, live coral cover dropped to 2-10%. One of the few reefs that kept live coral cover over 35% was Cayo Sombrero; nonetheless, the presence of some coral diseases has been detected within the past 2 years, representing a new source of coral mortality. Due to this situation, this study started a monitoring program on the incidence of coral diseases and syndromes in the reef of Cayo Sombrero. The CARICOMP protocol was used in order to evaluate reef health. Ten parallel band-transects (20 x 2m) where established at two depth intervals: Five between 3-8 m and five between 8-12 m, and the frequency of both, healthy and unhealthy colonies of each coral species was recorded along each band transect. In addition to other sources of coral damage (predation, siltation, etc), significant differences in disease incidence between the two depths intervals were tested with a Kruskall-Wallis test. The main problems observed were coral diseases such as yellow band (4,2%), dark spots (1.61%) and white plague-II (1.4%), mainly affecting Montastraea faveolata, M. annularis and Siderastrea siderea. Siltation, affecting massive colonies, such as Colpophyllia natans and Diploria strigosa; algae overgrowth, predation, anchor damage, and bleaching. Significant differences were found in the incidence of unhealthy (Kruskall-Wallis, p<0.05) bleached (Kruskall-Wallis, p < 0.05) and colonies affected by siltation (Kruskall-Wallis, p<0.05). More than 60% of the 585 coral colonies surveyed at both depths were found to be healthy, indicating that the Cayo Sombrero reef is still in good conditions compared to other localities in the Park. This study stresses the need to conduct early monitoring programs that survey coral disease incidence as a source of mortality for this coral reef.